(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate awareness among diabetic patients attending opd of National Institute of Diabetes and Endocrinology, Karachi, about the baseline blood glucose levels, Risk factors and Complications. Study Design: Cross-sectional study Place and Duration of Study: This study conducted at the OPD of National Institute of Diabetes and Endocrinology (NIDE), at OJHA campus of Dow University of Health Sciences, Karachi from January to March 2016 in Karachi. Materials and Methods: Adult, age 18 years and above, cases of diabetes were recruited from OPD of National Institute of Diabetes and Endocrinology (NIDE), at OJHA campus of Dow University of Health Sciences, Karachi. Data was collected using a structured questionnaire which was translated into local language i.e. Urdu. SPSS was used for statistical analysis. Results: A total of 100 participants completed the interview out of which 53% were male and 47% were female. Mean age of the participants was 49.3 ±10.7 years. Regarding the knowledge about target blood glucose levels, only 39% of the participants correctly identify the fasting blood glucose level while only 26% correctly answered random blood glucose levels. Overall mean score of knowledge and awareness was 40%. Male had better knowledge then female. Mean score for male was 50% compared to 30% among female. This difference was statistically significant p-value <0.05. Over all 45% of the participants were found to have poor knowledge scores, 35% had acceptable while only 20% had acceptable knowledge scores. Conclusion: This study found that there is low level of awareness among the patients attending diabetic outpatient clinics of NIDE. This indicates gaps in the patient care which needs attention. There is need to integrate patient education regarding glycemic targets, risk factors, complications and self-care as essential component of care through different channels of communication.